GAMBARAN PERSEPSI PENYAKIT TERHADAP KESEHATAN FUNGSI PARU PADA PASIEN ASMA DI SURABAYA - Amelia Lorensia; Rivan Virlando Suryadinata; Richa Ratnasari (The Indonesian Journal of Public Health, 2019)
Asthma could affect quality of life and decrease productivity. The worsening of asthma symptoms also affected lung function. Symptoms of asthma could be control by self-management. The patient's behavior in self-management influenced by his perception of asthma.  This research aims to determine  effect of perception of disease on health function of parents in asma patients in surabaya. Research using observational methods with cross sectional design. Research Subjects were outpatient asthma patients aged 17-25 years. Data collection was conducted from June 2015 to January 2016 in Surabaya, to 27 people.  Assessment of asthma perception use Illness Perception Questionnaire (IPQ) and health condition of lung function with peak flow meter to assess PEF (peak expiratory flow). The results of this study indicate that both groups have a PEF value <50% of the estimated PEF value. The data showed no significant difference (p (0.766)> 0.05) between disease perceptions based on the number of asthma-related symptoms with lung function (PEF), with the greatest answer as the cause of asthma that is genetic. Therefore, the perception of asthma does not affect lung function (PEF) in adult asthma patients in Surabaya.